The Socio-hydrological Impacts of Oil Palm Plantations on Integrated Watershed Management:: Insights from Malaysia and Ways Forward - Taishi Yazawa; Yoshihisa Shimizu (The Journal of Indonesia Sustainable Development Planning, 2020)
This paper aims to investigate the feasibility offlood management based onthe concept of Integrated Watershed Management (IWM) via a literature review and field surveys. The investigationfocused on the primary industry of oil palm plantations in Malaysia. Although the country is promoting the palm oil industry, the impact of oil palm plantations on the local environment has been relatively disregarded because of the benefits and opportunities, such as subsidies, jobs, and amenities,which the local companies/people can obtain. Effective flood management inoil palm plantations entails the local peoples’ understanding and participation in the management activities, such as removing fallen leaves and weeding an area. Theflood management strategiessuggested inthis research provide new insights into local flood management, which usually focuses on the hydrologic aspects, by promoting the integration of the actual-local environment and local people’s actions for their environment within the framework of IWM.